Beyond Placement of Pedicle Screws - New Applications for Robotics in Spine Surgery: A Multi-Surgeon, Single-Institution Experience - Tabarestani, Troy Q.; Sykes, David; Murphy, Kelly R.; Wang, Timothy Y.; Shaffrey, Christopher I.; Goodwin, C. Rory; Horne, Phillip; Than, Khoi D.; Abd-El-Barr, Muhammad M. (Frontiers in Surgery, 2022)
Interest in robotic-assisted spine surgery has grown as surgeon comfort and technology has evolved to maximize benefits of time saving and precision. However, the Food and Drug Administration (FDA) has currently only approved robotics to assist in determining the ideal trajectory for pedicle screw placement after extensive research supporting its efficacy and efficiency. To be considered a durable and effective option, robotics need to expand beyond the indication of just placing pedicle screws. This article aims to illustrate a multi-surgeon, single-institution experience with unique applications of robotic technologies in spine surgery. We will explore accessing Kambin’s Triangle in percutaneous transforaminal interbody fusion (percLIF), iliac fixation in metastatic cancer, and sacroiliac (SI) fusions. Each of these topics will be covered in depth with associated background information and subsequent discussion. We show that with proper understanding of its limitations, robots can help surgeons perform difficult surgeries in a safe manner.